Pacific island tropical cyclones are more frequent and globally relevant, yet less studied - Marler, Thomas E. (Frontiers in Environmental Science, 2014)
Typhoon Haiyan devastated the Philippines in 2013 and illuminates the fact that the majority of tropical cyclone (TC) research has focused on the Atlantic Basin, continental socio-ecological systems, affluent regions where the resilience attributes of the human element differ from that of the of majority the world’s population, and organized countries where research and relief capacities are among the best worldwide. I contend that this collective international bias minimizes the usefulness of global TC research in light of global change forecasts, which predict increased frequency of intense TCs. Moreover, paleoecological studies indicate ecosystem resilience following a TC is greatly increased within habitats that experienced a prior history of frequent TCs. When these retrospective and future visions are connected, science-based analysis of the influences of climate change on TC disturbance argues for an increase in contemporary research on TCs of developing island nations in the western Pacific where TCs are already relatively frequent. Otherwise the current research trajectory may further widen the disconnect between best available science and future management decisions.